Teach the children well: young adult literature and queer content - Billingham, Susan E. (University of Nottingham, 2013)
This paper forms part of a larger project interested equally in literary analysis of young adult texts with LGBTQ content, the institutional contexts within which such texts are produced, and what happens to the texts once they are published. Ultimately, I aim to investigate the extent to which works with queer-positive content are being incorporated into school classrooms and libraries. The current working paper compares Shyam Selvadurai’s Swimming in the Monsoon Sea (2005) with Nancy Garden’s Good Moon Rising (1996), two young adult novels from opposite sides of the Canada-U.S. border that prominently feature student productions of canonical plays as part of their narratives. Close analysis of the use made of these dramatic intertexts illuminates the intersections between education, family, nation and literary canons in the surveillance of adolescent sexual citizenship.